UTILIZATION OF AMMONIUM HYDROXIDE COMPOUND AS CARBOSORB - Andi Tenrisa’na; Muhammad Zakir; Maming Maming (Marina Chimica Acta, 2015)
tilization Of Ammonium Hydroxide Compound As Carbosorb For Measurement Of Carbon-14 In Determination Age Of Coral Reef Sample has been performed. The objective of this research is to Determine the age of Coral Sample of Spermonde Islands through Activity Measurements of carbon-14 with LSC (Liquid Scintillation Counting) method. Coral sample were taken from around Langkai Island. The steps of this research are: Sample preparation, CO2 absorption with solution of MEA, DEA and TEA and measurement of carbon-14 activity using Liquid Scintillation Counter (LSC) Hidex 300 SL. Absorption CO2 using ammonium hydroxide. The specific activity of coral sample using carbosorb ammonium hydroxide was 14.43 ± 1,2 DPM/g C. The age of coral sample calculated from the specific activity using carbosorb ammonium hydroxide was 484.63 ± 54 years.Keywords : LSC (Liquid Scintilation Counter), Carbon-14, CO2 Absorption, Ammonium hydroxide, Langkai Island